2020
DOI: 10.1126/science.abd2109
|View full text |Cite
|
Sign up to set email alerts
|

Neuron class–specific responses govern adaptive myelin remodeling in the neocortex

Abstract: Cellular effects of visual deprivation Myelination speeds the progress of action potentials along neuronal axons. Yang et al. studied changes in myelination in the mouse visual cortex in response to visual experience (see the Perspective by Yalçin and Monje). With normal vision, myelination is continuously remodeled. As ocular dominance shifts in response to monocular deprivation, myelination patterns change on certain inhibitory interneurons but not on excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 39 publications
4
75
0
Order By: Relevance
“…The interplay between oligodendrocyte-lineage cells and PV+ neurons, in particular during developmental windows of plasticity, are being increasingly documented 59 . Interestingly, OPCs have been shown to be ontogenetically related to PV+ neurons 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between oligodendrocyte-lineage cells and PV+ neurons, in particular during developmental windows of plasticity, are being increasingly documented 59 . Interestingly, OPCs have been shown to be ontogenetically related to PV+ neurons 60 .…”
Section: Discussionmentioning
confidence: 99%
“…One previous study found even very subtle defects in myelination have a persistent impact on cortical network functions [17]. In addition, intra-cortical myelin is a sensitive indicator to track the development of neuronal activity throughout the lifespan, thus actively engaged in brain remodeling and plasticity [13,15,18]. Together, these findings suggest that intra-cortical myelination is essential for fine-tuning cortical functional circuits.…”
Section: Introductionmentioning
confidence: 91%
“…Myelinated axons, also located in cerebral cortex gray matter, are called intra-cortical myelin. Intra-cortical myelin is of great importance for the integrity of neural connections and neural synchrony of the cerebral cortex [12][13][14][15]. In humans, direct evidence suggests intra-cortical myelin is involved in cognitive functioning through its relationship with neural activity, potentially by the facilitation of local neural synchrony [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested that the effects of neuronal activity on myelination are mediated by the release of synaptic vesicles, 17 , 18 including in a neuron-subtype-specific manner. 19 , 20 For example, in zebrafish, blocking vesicular fusion from specific neurons reduced myelin sheath number and length along their axons. 18 , 20 Furthermore, live-imaging studies revealed that synaptic vesicles can accumulate along axons during myelination, 18 , 21 , 22 leading to the model that vesicular cargo directly drives myelin sheath formation and/or growth.…”
Section: Introductionmentioning
confidence: 99%